Power converting sizing tools for dual active bridge DC-DC converter - Wood, Laura Eilidh (2016)
This paper analyses and sizes a dual active bridge (DAB) DC-DC converter. Firstly, an understanding of DAB DC-DC converters and transformer and inductor sizing is gained. With set requirements for the converter, unknown parameters are calculated. This allows a schematic of the converter to be built and simulated using LTSpice software. An iterative process is used to determine the ideal value for the output capacitor by observing the output voltage. The schematic is used to finalise parameter values and to confirm the DC-DC converter is behaving as expected. Conduction and switching losses are also calculated. These are used to determine the efficiencies of both converters. Using Mathematica software the relationships between switching frequency, output power, output voltage and inductor size are next explored. Mathematica is then used to create a sizing tool. The sizing tool can be used to compare the previously calculated currents across the transformer and switches to their expected values. Next, Mathematica and the schematic’s parameters are used to determine a suitable core for the inductor and transformer. Once the core has been selected the overall mass of the converter is determined. Finally, the sizing tool is used to observe the inductance and overall mass of the DC- DC converter over a range of switching frequencies. The inductance and mass of the inductor and transformer decreases as the switching frequency increases.